PENGEMBANGAN BAHAN AJAR BERBASIS PENDIDIKAN KARAKTER - Zahra Alwi; Ernalida Ernalida; Yenni Lidyawati (Jurnal Inovasi Sekolah Dasar, 2020)
AbstractThe problems discussed in this paper are, "How are the teaching materials that can push towards the creation of human beings who have IPTEK and also IMTAQ, facing the challenge of the Industrial Revolution of 4.0?" Elementary school teacher Education is one of the important containers to make the world of education play a role in facing the challenges of the current revolution. For that it needs to be developed and compiled the latest teaching materials based on character education. By preparing teaching materials that contain character education values that are in line with the access of learning and curriculum, will be produced graduates who not only have high knowledge and skills, but also have a attitude, personal and social, which is capable. Through the literature and research results, in this paper presented product development based on character education, which can be a reference for the development and preparation of teaching materials at the basic level, as a shoulder effort in the planting of positive attitudes to learners.  Keywords: teaching materials, character education, IPTEK and IMTAQ, the challenge of Industrial revolution Abstrak            Permasalahan yang dibahas dalam makalah ini adalah, “Bagaimanakah bahan ajar yang dapat mendorong ke arah terciptanya insan-insan yang memiliki IPTEK sekaligus juga IMTAQ, menghadapi tantangan revolusi industri 4.0?” Pendidikan Guru Sekolah Dasar merupakan salah satu wadah yang sangat penting untuk menjadikan dunia pendidikan berperan dalam menghadapi tantangan revolusi saat ini. Untuk itu perlu dikembangkan dan disusun bahan ajar yang mutakhir yang berbasis pendidikan karakter. Dengan menyiapkan bahan ajar yang memuat nilai-nilai pendidikan karakter yang sejalan dengan capaian pembelajaran dan kurikulum, akan dihasilkan lulusan yang tidak hanya memiliki pengetahuan dan keterampilan yang tinggi, tetapi sekaligus memiliki sikap, personal dan sosial, yang mumpuni. Melalui kaji literatur dan hasil penelitian, dalam makalah ini disajikan produk hasil pengembangan berbasis pendidikan karakter, yang dapat menjadi acuan untuk pengembangan dan penyusunan bahan ajar di tingkat dasar, sebagai upaya yang pundamen dalam penanaman sikap-sikap positif kepada pembelajaran. Kata-kata kunci: bahan ajar,  pendidikan karakter, IPTEK dan IMTAQ, tantangan revolusi    industri